Contribution of zooplankton to vertical carbon fluxes in the Kara and White Seas. - Kosobokova, Ksenia N; Martynova, Daria M; Prudkovsky, Andrey (PANGAEA, 2011)
Data on the zooplankton community structure, gut evacuation rate and carbon content of zooplankton faecal pellets were used for assessing the contribution of zooplankton to vertical carbon fluxes in the White and Kara Seas. The results revealed strong regional and seasonal variations of pellet carbon input related to differences in structure and dynamics of the zooplankton communities in the regions studied. In the deep regions of the White Sea, maximum daily pellet carbon flux from the 0-50 m layer was observed in the spring. It reached 98 mg Corg m-2 day-1 and coincided with a strong predominance of the large arctic herbivorous copepod Calanus glacialis in the surface layers. In summer and fall, it decreased by 1 to 2 orders of magnitude due to migration of this copepod to its overwintering depths. In contrast, in the shallow coastal regions, the pellet production was low in spring, gradually increased during summer and reached its maximum of 138 mg Corg m-2 day-1 by late summer to beginning of autumn. Such a seasonal pattern was in accordance with the seasonal variation of abundance of major pellet producers, the small boreal copepods Acartia bifilosa, Centropages hamatus, and Temora longicornis. In the estuarine zone of the Kara Sea, the pellet flux was mostly formed by pellets of brackish-water omnivorous copepods. It varied from 35 mg Corg m-2 day-1 in 1997 to 96 mg Corg m-2 day-1 in 1999. In the central Kara Sea with its typical marine community, the daily flux reached 125 mg Corg m-2 day-1 in summer. The results of our calculations indicate that both in the White and Kara seas zooplankton pellet carbon contributes up to 30 % to the total carbon flux during particular seasons.
Tab. 1: Chupa Inlet, Kandalaksha Bay of the White Sea. Population density of the dominant boreal copepod species and daily pellet carbon flux
Keywords: Acartia bifilosa; Cape Kartesh, White Sea; Centropages hamatus; Copepoda, fecal pellet flux; DEPTH, water; EXP; Experiment; Fecal pellet carbon flux; RAS; Temora longicornis